INTRARENAL ENERGY METABOLISM CHANGES IN CONDITIONS ACUTE EXPERIMENTAL PYELONEPHRITIS COMPLICATED BY HYPERGLYCEMIA WITH PHARMACOLOGICAL CORRECTION - Borisov, S.О.; Kostev, F.I.; Borisov, O.V.; Mikheytseva, I.M.; Kolomiichuk, S.G.; Shostak, M.V.; Tiron, O.I. (World of Medicine and Biology, 2024)
The purpose of the study was to establish the role of energetic metabolism indexes in the pathogenesis of acute pyelonephritis with concomitant diabetes mellitus in an experimental condition with pharmacological correction. Acute pyelonephritis alone and being complicated by a hyperglycemic state reproducing diabetes mellitus I and II types were modeled in rats. Rats with acute pyelonephritis complicated by diabetes mellitus I and II types received both etiotropic drug influence and etiopathogenetic drug influence for 14 days. The content of lactate, pyruvate, glucose-6-phosphate, ATP, and ADP, together with the NAD/NADH ratio, were studied in the kidneys of rats 28 days after the trial started. The comorbid hyperglycemic state on the background of acute pyelonephritis contributes to rats’ kidney energy disorders' progress manifested by lactate level increase and pyruvate, glucose-6-phosphate, and ATP levels decrease. Further progression of energy metabolism disorders was found in the kidneys of rats with acute pyelonephritis with concomitant diabetes mellitus, especially of the I type. Such energetic chaos manifested in the form of ATP reserves depletion, which may be associated with ATP-impaired synthesis that intensifies hyperglycemia and contributes to both intrarenal hypoxia and acidosis development. Succinate-containing compounds and a ribonucleic acid donor combined administration cause a restorative impact on energy metabolism indexes in kidney tissue in acute pyelonephritis complicated by diabetes mellitus. The results of the study indicated the reasonability of succinate-containing compounds and ribonucleic acid donors’ co-administration in clinical conditions to normalize lactate, pyruvate, and energy potential content in patients with acute pyelonephritis with concomitant diabetic kidney damage.
Keywords: acute pyelonephritis; streptozotocin-induced diabetes; rats; energy metabolism; drug correction